Oxidative Coupling of Methane Using Mg/Ti-Doped SiO2-Supported Na2WO4/Mn Catalysts - Yunarti, Rika Tri; Gu, Sangseo; Choi, Jae-Wook; Jae, Jungho; Suh, Dong Jin; Ha, Jeong-Myeong (American Chemical Society, 2017)
The oxidative coupling of methane (OCM) was performed using Na2WO4/Mn catalysts supported on Mg/Ti/Si mixed oxides. Na2WO4/Mn/Mg0.05Ti0.05Si0.90On exhibited a 23.1% C-2. yield at 800 degrees C, which is a 35% higher C-2 yield than that obtained using conventional Na2WO4/Mn/SiO2 in this study. The formation of Mg/Ti-doped a-cristobalite SiO2 was observed for supported Na2WO4/Mn catalysts, and their improved catalytic activity could be attributed to the suppressed incorporation of Na/W/Mn compounds into the alpha-cristobalite SiO2 structure and the existence of OCM-active Na/W/Mn compounds exposed on the support surface. X-ray diffraction, X-ray photoelectron spectroscopy, Raman spectroscopy, and O-2-temperature-programmed desorption were performed in an effort to understand the improved catalytic OCM activity of Mg/Ti-doped SiO2-supported Na2WO4/Mn catalysts.
Keywords: ANAEROBIC-DIGESTION; C-2 HYDROCARBONS; NATURAL-GAS; MN/NA2WO4/SIO2; CONVERSION; BIOGAS; STATE; PERFORMANCE; TRANSITION; OXYGEN